2017
DOI: 10.1097/coc.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose-Escalation Study of Weekly Paclitaxel and Cisplatin Followed by Radical Hysterectomy in Stages IB2 and IIA2 Cervical Cancer

Abstract: Weekly paclitaxel and cisplatin NAC for 3 courses can be tolerated with excellent short-term outcome. With the caveat of small number of patients, this study supports future phase II trials of weekly paclitaxel and cisplatin NAC for 4 to 5 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Currently, the main therapies used for patients with CSCC include surgery followed by adjuvant therapy [2][3][4]. The present study suggested that TUSC3 may act as a potential tumor suppressor gene in CSCC, which revealed a unique Janus-like character in cancer pathogenesis and development.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Currently, the main therapies used for patients with CSCC include surgery followed by adjuvant therapy [2][3][4]. The present study suggested that TUSC3 may act as a potential tumor suppressor gene in CSCC, which revealed a unique Janus-like character in cancer pathogenesis and development.…”
Section: Discussionmentioning
confidence: 56%
“…However, it is still a major public health problem in developing countries [1,2]. Generally, the major therapeutic modality for cervical squamous cell carcinoma (CSCC) (FIGO stage IA2-IIA) is radical hysterectomy and pelvic lymphadenectomy [2][3][4]. The aggressiveness of tumor cells is closely associated with the prognosis of patients with cervical cancer [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…For stage IB2/IIA2 cervical cancer, concurrent chemoradiotherapy and radical hysterectomy + individualized postoperative adjuvant therapy were acceptable treatments, while the FIGO and NCCN guidelines indicated that because of the large diameter of IB2/IIA2 cervical cancer, the possibility of supplementing high and intermediate risk factors for radiotherapy after surgery was high, so platinum‐based concurrent chemoradiotherapy was a better choice for patients with IB2/IIA2 cervical cancer 1, 3 . In Europe, South Korea, China, and Japan, there have been reports of surgical treatment of patients with stage IB2/IIA2 cervical cancer, 9, 19–21 but they paid more attention to laparoscopic conditions such as bleeding volume, operation time, intraoperative postoperative complications, etc. There was no multicenter large‐scale report on tumor prognosis without preoperative adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The chemotherapy regimen used at BSMMU with cisplatin and paclitaxel is currently thought to be one of the most efficacious [18] [19]. The hope is that neoadjuvant chemotherapy (NACT) will improve prognosis of patients with early bulky cervical cancer.…”
Section: Discussionmentioning
confidence: 99%